Autoethnography as Writing Representation in Cultural Sport Psychology - Rahayuni, Kurniati (KnE Social Sciences, 2022)
Cultural sport psychology (CSP) focuses on the interplay between culture and sport, which often discuss marginalised topics or sports practice in a specific population. This article suggests using autoethnography as a means of representing CSP research in the field. This article will explore what autoethnography is, why it is suitable for CSP, guidance on how to conduct autoethnography in the field of sport, exercise, health and related fields, and ethical considerations to be made when writing an autoethnography. Keywords: culture, autoethnography, qualitative, sport and exercise psychology